Introducing undergraduate students to human evolution through eco-immunology - Balgopal, Meena M.; Neuwald, Jennifer L.; Pandey, Sumali (Frontiers in Education, 2025)
IntroductionThe benefits of actively engaging students is especially relevant for teaching undergraduate students about evolutionary processes and content. Examining eco-immunological data can help students overcome the naïve conception that humans are not evolving or affected by evolutionary pressures.MethodsHere, we used graphical reasoning in two evolution courses (small/honors and large/regular) to teach students about eco-immunology in humans and non-human organisms during a unit on the evolution of life-history traits. The module challenged students to (i) distinguish between immunological and evolutionary fitness, (ii) evaluate graphical data from the primary scientific literature on energy allocation and trade-offs, and (iii) integrate these proximate and ultimate processes into a more wholistic understanding of on-going human evolution. Student performance and perceptions were measured through closed and open response items. Open response items were thematically analyzed to identify salient themes.ResultsStudent performance in the large class increased significantly on items related to fitness, energy trade-offs, and graphical reasoning, while student performance in the small class increased just for items related to energy trade-offs. Student confidence in graphical reasoning, perceptions of the importance of graphical reasoning, and perceptions of the value of interdisciplinary research was high for both classes. Student narrative examples regarding confidence, perceptions of graphical reasoning, and perceptions of interdisciplinary research are presented.DiscussionWe conclude that students can increase their performance and perceptions of eco-immunology and graphical reasoning through an active learning, graph reading module. Furthermore, students can be introduced to the field of immunology through their evolution courses.